Foam engineering : fundamentals and applications - Stevenson, Paul, 1973- (Chichester, West Sussex, UK : Wiley, 2012)
'Containing contributions from leading academic and industrial researchers, this book provides a much needed update of foam science research. The first section of the book presents an accessible summary of the theory and fundamentals of foams. This includes chapters on morphology, drainage, Ostwald ripening, coalescence, rheology, and pneumatic foams. The second section demonstrates how this theory is used in a wide range of industrial applications, including foam fractionation, froth flotation and foam mitigation. It includes chapters on suprafroths, flotation of oil sands, foams in enhancing petroleum recovery, Gas-liquid Mass Transfer in foam, foams in glass manufacturing, fire-fighting foam technology and consumer product foams. Key features: Foam fractionation is an exciting and emerging technology, starting to gain significant attention. Discusses a vital topic for many industries, especially mineral processing, petroleum engineering, bioengineering, consumer products and food sector. Links foam science theory to industrial applications, making it accessible to an engineering science audience. Summarizes the latest developments in this rapidly progressing area of research. Contains contributions from leading international researchers from academia and industry'--
Includes bibliographical references and index.
Keywords: Foam; Foam -- Industrial applications; Foam -- Technological innovations; Foamed materials